Simulation Study on the Performance and Emission Parameters of a Marine Diesel Engine - Xin, Rongbin; Zhai, Jinguo; Liao, Chang; Wang, Zongyu; Zhang, Jifeng; Bazari, Zabihollah; Ji, Yulong (Journal of marine science and engineering, 2022)
Development of intelligent ships requires marine diesel engine simulation models of high accuracy and fast response. In addition, with advent of tighter shipping air emissions regulations, such models are required to have emission prediction capabilities. In this article, such a model was developed and validated for a 30,000-ton bulk carrier main engine using MATLAB/Simulink. The simulation is based on mean value model, which predicts both the steady-state and dynamic performance of the engine. The results show that the steady-state performance parameters of the main engine are predicted within 2.2% error, and the exhaust emissions parameters are predicted within 7% error as compared to the bench test data from the engine manufacturer. The Maximum Continuous Rating (MCR) points at 100%, 75%, 50% and 25% of the E3 duty cycle were investigated with emphasis according to the diesel propulsion characteristics. In dynamic simulation, it is found that the compressor pressure fluctuation is greater than that of the exhaust pressure with the load variation. Furthermore, the compressor and the exhaust pipe have a similar temperature drop value (about 60 K) when the engine load changes from 100% to 50% MCR, and the exhaust pipe temperature fluctuation is more significant when the load varies from 50% to 25% MCR. The above results show the model’s good transient capability in simulating the dynamic characteristics of the engine. This model can be used especially for the development and control of marine diesel engines in intelligent ships as well as training-oriented marine engine and ship simulators.